2010
DOI: 10.1063/1.3391921
|View full text |Cite
|
Sign up to set email alerts
|

Development of asymmetric double probe formula and its application for collisional plasmas

Abstract: The ratio of the electron and ion saturation currents in single probe I-V characteristics for microwave-sustained plasma jets at atmospheric pressure are found to be much smaller than the value expected from the standard high-pressure single probe theory providing an over estimation of electron temperatures. By assuming that the single probe characteristic behaves as an asymmetric double probe when the electron to ion saturation current ratio is reduced, the whole characteristics may be fitted and significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…From these figures it is observed that the temperature estimated by ADP theory [16,17] decreases with increasing the probe position from the nozzle head for both the gas species as expected, which is the opposite pattern getting from the HSP theory [15] ensuring the reliable plasma parameters estimated by ADP theory [16,17]. The electron temperature estimated by the ADP theory [16,17] is found to be in the range of 1.2∼1.5 eV in the case of Ar plasmas while 0.9∼3 eV in the case of He plasmas indicating that ADP theory provides more reasonable values of plasma parameters. Figure 7 shows the comparison of electron density, N e of He plasma jet estimated by HSP theory [15] and ADP theory [16,17] under the quasi-neutrality condition N e = N i , where N i is the ion density.…”
Section: Estimation Of Plasma Parametersmentioning
confidence: 98%
See 4 more Smart Citations
“…From these figures it is observed that the temperature estimated by ADP theory [16,17] decreases with increasing the probe position from the nozzle head for both the gas species as expected, which is the opposite pattern getting from the HSP theory [15] ensuring the reliable plasma parameters estimated by ADP theory [16,17]. The electron temperature estimated by the ADP theory [16,17] is found to be in the range of 1.2∼1.5 eV in the case of Ar plasmas while 0.9∼3 eV in the case of He plasmas indicating that ADP theory provides more reasonable values of plasma parameters. Figure 7 shows the comparison of electron density, N e of He plasma jet estimated by HSP theory [15] and ADP theory [16,17] under the quasi-neutrality condition N e = N i , where N i is the ion density.…”
Section: Estimation Of Plasma Parametersmentioning
confidence: 98%
“…Finally, in order to overcome the limitations of HSP theory [15], we analyze the measured probe characteristics using the recently developed asymmetric double probe (ADP) theory [16,17], and compare the plasma parameters with those estimated by single probe theory [15]. The axial profile of electron temperature, T e of Ar and He plasmas estimated by HSP [15] and ADP theory [16,17] are compared in Fig.…”
Section: Estimation Of Plasma Parametersmentioning
confidence: 99%
See 3 more Smart Citations